PENGARUH KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI STUDY PADA KANTOR PUSLITBANG PERHUTANI CEPU - Devi Kurniawati, 14.05.51.0132; Suko Priyono, Bambang (Students' Journal of Economic and Management, 2018)
This study aims to examine the influence of leadership, motivation, and work discipline on employee performance. Subjects in this study are employees who work at the Office of Research and Development of Perhutani Cepu. Sampling was done by using the sampling method and the number of samples was 80 respondents and only processed as much as 71. The retrieval method was primary data using questionnaire method by distributing questionnaires addressed by respondents at the Research and Development Center of Perhutani Cepu to obtain information. Data analysis using validity test, reliability test, regression analysis, multiple regression analysis. The results of this study indicate that (1) Leadership has a positive and significant effect on employee performance, (2) Motivation has a positive and insignificant effect on employee performance, (3) Work discipline has a positive and significant effect on employee performance. Keywords: Leadership, Motivation, and Work Discipline, Against Employee Performance